Kerja Sama Perdagangan Barang pada Forum RCEP bagi Indonesia [Cooperation of Goods Trading on Rcep Forum for Indonesia] - Ragimun Abdullah (Pusat Penelitian, Badan Keahlian DPR RI, 2018)
Regional Comprehensive Economic Partnership (RCEP) was formed as a manifestation of ASEAN’s response to the economic dynamics in the region as well as globally, in the format of integration of ASEAN countries with the global economy. The RCEP has a progressive goal of eliminating tariffs and non-tariff barriers, and facilitating and enhancing transparency among members. The unification of 16 countries under a free trade agreement scheme would be make the RCEP a large trading bloc, that holds one-third of the world. The objective of this study is to analyze the optimization of trade in goods with the enactment of RCEP and efforts that can be done to optimize the benefits of trade in goods for Indonesia. In this research, the economic approaches are use to emphasized the impact of RCEP formation on trade of goods for Indonesia through descriptive approach. The result of the study are, the optimization of Indonesia’s medium and long-term export increase can be achieved, by the acceleration of the resolution of the RCEP negotiations, especially on three important issues, namely trade in goods, trade in services, and investment. The other efforts that should be taken were to encourage the transformation of export structures from commodity-based to value-added products and services, utilizing all existing preferences schemes regarding the opening of access market especially specific target markets requests by Indonesian delegates. Furthermore, it should always focus on economis of scale to improve trade balance and compile the negative list of export destination countries which need to be optimized such as China, Japan and South Korea.Keywords: RCEP, optimization of cooperation, mutual benefitAbstrakRegional Comprehensive Economic Partnership (RCEP) dibentuk sebagai wujud dari respon ASEAN terhadap dinamika ekonomi di kawasan dan global berupa integrasi negara-negara ASEAN dengan perekonomian global. RCEP memiliki tujuan progresif menghapuskan tarif dan hambatan non-tarif serta memfasilitasi dan meningkatkan transparansi antar negara anggota. Penyatuan 16 negara dalam satu skema perjanjian perdagangan bebas akan menjadikan RCEP menjadi blok perdagangan besar yang menguasai sepertiga dunia. Penelitian ini bertujuan menganalisis optimalisasi perdagangan barang dengan diberlakukannya RCEP dan upaya-upaya yang dapat dilakukan untuk mengoptimalkan manfaat atas perdagangan barang bagi Indonesia. Dalam penelitian ini digunakan pendekatan-pendekatan ekonomi yang lebih menekankan pada dampak pembentukan RCEP terhadap perdagangan barang bagi Indonesia melalui pendekatan deskriptif. Sebagai hasilnya adalah bahwa optimalisasi peningkatan ekspor Indonesia jangka menengah dan jangka panjang akan dapat dicapai, salah satu upaya yang dapat dilakukan adalah melalui percepatan penyelesaian perundingan RCEP khususnya terkait tiga isu penting yaitu isu perdagangan barang (trade in goods), perdagangan jasa (trade in services), dan investasi. Upaya-upaya lainnya adalah mendorong transformasi struktur ekspor dari berbasis komoditi menjadi produk dan jasa yang bernilai tambah, memanfaatkan seluruh skema preferensi yang ada selama ini dan request delegasi Indonesia terkait pembukaan akses pasar dengan menargetkan pasar secara spesifik. Demikian juga senantiasa fokus pada skala untuk membantu perbaikan neraca perdagangan serta menyusun “negative list” beberapa negara tujuan ekspor yang selama ini perlu dioptimalkan seperti Cina, Jepang dan Korea Selatan.Kata kunci: RCEP, optimalisasi kerja sama, saling menguntungkan